Mutations of cytochrome c identified in patients with thrombocytopenia THC4 affect both apoptosis and cellular bioenergetics. - De Rocco, Daniela; Cerqua, Cristina; Goffrini, Paola; Russo, Giovanna; Pastore, Annalisa; Meloni, Francesca; Nicchia, Elena; Moraes, Carlos T; Pecci, Alessandro; Salviati, Leonardo; Savoia, Anna (Biochim Biophys Acta, 2014)
Inherited thrombocytopenias are heterogeneous diseases caused by at least 20 genes playing different role in the processes of megakaryopoiesis and platelet production. Some forms, such as thrombocytopenia 4 (THC4), are very rare and not well characterized. THC4 is an autosomal dominant mild thrombocytopenia described in only one large family from New Zealand and due to a mutation (G41S) of the somatic isoform of the cytochrome c (CYCS) gene. We report a novel CYCS mutation (Y48H) in patients from an Italian family. Similar to individuals carrying G41S, they have platelets of normal size and morphology, which are only partially reduced in number, but no prolonged bleeding episodes. In order to determine the pathogenetic consequences of Y48H, we studied the effects of the two CYCS mutations in yeast and mouse cellular models. In both cases, we found reduction of respiratory level and increased apoptotic rate, supporting the pathogenetic role of CYCS in thrombocytopenia.
Keywords: Amino Acid Sequence; Animals; Apoptosis; Base Sequence; Cells, Cultured; Child, Preschool; Cytochromes c; DNA Mutational Analysis; Embryo, Mammalian; Energy Metabolism; Family Health; Female; Fibroblasts; Humans; Lung; Male; Mice; Molecular Sequence Data; Mutation, Missense; Oxygen Consumption; Pedigree; Saccharomyces cerevisiae; Sequence Homology, Amino Acid; Thrombocytopenia